Capacity of second spillway of Boguchanskaya HPP - Gouriev A. P.; Khanov N. V.; Fartukov V. A.; Zborovskaya M. I.; Abidov M. M. (E3S Web of Conferences, 2023)
The main problem in designing the discharge of water flow from the upstream to the downstream is to ensure the capacity of spillway structures. This article discusses the design options for the design top of the spillway: with water diversion through a short nozzle in the pressure mode and energy dissipation in stilling basin, with the pressure-free and pressure-free passage of water through spillway No. 2 and damping of the flow energy by jet discharge into the lower stream by the inclined face of the threshold in the stilling basin; with no pressure passage and pressure passage of water through spillway No 2 and energy dissipation of the flow by throwing the flow discharge into the downstream by the inclined face of the threshold of a stilling basin; with the passage of building expenses through the sill in no pressure and pressure-type short-nozzle modes, with the spillway No. 2’s horizontal water outlet at the level of 139.5 m, with a jet discharge by a toe-springboard at an angle of 35°, and with the outlet rib's mark of 143.8 m. This article aims to obtain the flow characteristics of the considered spillway option for the period of temporary operation of the hydrotechnical complex.